PEMANFAATAN LAHAN TIDUR UNTUK MENINGKATKAN USAHA PERTANIAN DI KELURAHAN WALIAN SATU KOTA TOMOHON - Grace A. J. Rumagit; Melsje Yellie Memah (AGRI-SOSIOEKONOMI, 2018)
The purpose of the Community Partnership Program (PKM) in utilizing of idle land to increase agricultural business is to improve community welfare through diversification of agricultural businesses on idle land. This research was conducted in Walian Satu Village, South Tomohon Subdistrict, Tomohon City, for 10 months from February to November 2018 at Wawo farmer groups and Sapa farmer groups, each with 5 members so that the total members were 10 people. Criteria for achieving community partnership program activities (PKM) are: (1) land processing skills, (2) number and quality of production, (3) marketing, (4) income of group members, and (5) institutions and management. The results achieved through the community partnership program (PKM) are (1) increasing knowledge and skills of farmer group members in managing land. The expertise and knowledge possessed by farmer groups now has increased and has an effect on productivity and agricultural products, (2) intensive farming extention and supporting carried out by the team makes farmer groups experience increased insight in farming to be more increasing, both in its number and quality. (3) Limitations in funding make farmers difficult to manage land and choose to find other jobs. However with the funding from DP2M DIKTI, land management can be done well and farmer groups can develop their agricultural businesses and marketing. (4) Obstacles in cultivating of land and the desire to change professions are no longer the main thing due to various assistance in the form of seeds, agricultural equipment, funding, farming extention and supporting by the PKM team to develop agricultural businesses so that their income increases. (5) Debriefing knowledge about management and group institutions makes farmer groups better able to manage their farming.*jnkd*.